Capacity‐oriented approaches to developing childhood obesity interventions: a systematic review. Issue 2 (10th December 2017) - Foster, B. A.; Fu, E.; Bendiks, N.; Gaspard, C. S.; Sharifi, M.
Summary: Capacity‐oriented approaches to health interventions seek to empower the target population or community to manage the health issue themselves using resources they can control. Positive deviance, resilience and asset‐based approaches are three such methods of developing and implementing health interventions. This study aimed to review the efficacy of interventions explicitly applying these methods in addressing childhood obesity using adiposity as the primary outcome, measured by standardized body mass index. The search strategy was developed and implemented across four electronic databases. Of the 181 records identified and screened, 11 studies were identified as using a capacity‐oriented approach overall. Asset‐based approaches ( n = 8 studies) consisted of 47 880 participants, positive deviance ( n = 2 studies) consisted of 781 participants, and resilience‐based interventions ( n = 1 study) consisted of 35 participants. The asset‐based approaches were mixed, with three of the eight studies showing a significant reduction in adiposity, while the other five did not find a difference. The positive deviance and resilience‐based studies showed signs of efficacy in reducing adiposity. There was significant design heterogeneity across studies, and varied interpretations and definitions of the approaches were used. Further work should attempt to achieve some consensus on the use of these approaches to facilitate comparison and advance the science of capacity‐oriented interventions for childhood obesity.